2018
DOI: 10.1177/2156759x19857921
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Yoga into a Comprehensive School Counseling Program: A Qualitative Approach

Abstract: Using an exploratory phenomenological qualitative research design, this study investigated the lived experiences of 10 school counselors who integrate yoga into their comprehensive school counseling programs. Analysis of data revealed five significant themes and subsequent subthemes describing the participants' lived experiences of yoga integration within their school counseling programs. We include implications for research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, alignment between MTSS and CSCPs leads to more efficient use of school counselors' time and increased leadership capacity (Betters-Bubon & Donohue, 2016;Goodman-Scott & Ockerman, 2019). Another study by Scarborough et al (2015) found that students who received counseling services as part of a comprehensive school counseling program aligned with MTSS had higher attendance rates and fewer behavioral incidents than those who did not receive such services.…”
Section: Mtss and School Counselingmentioning
confidence: 99%
“…Furthermore, alignment between MTSS and CSCPs leads to more efficient use of school counselors' time and increased leadership capacity (Betters-Bubon & Donohue, 2016;Goodman-Scott & Ockerman, 2019). Another study by Scarborough et al (2015) found that students who received counseling services as part of a comprehensive school counseling program aligned with MTSS had higher attendance rates and fewer behavioral incidents than those who did not receive such services.…”
Section: Mtss and School Counselingmentioning
confidence: 99%
“…The role of school counselors has shifted from providing academic and vocational guidance for individual students to being agents of change in comprehensive school counseling programs addressing the academic, career, and social/emotional needs of all students (ASCA, 2012). School counselors have taken on the challenge of integrating wellness and social/emotional learning into school-wide programs to meet the needs of all students (Taylor et al, 2019), and they are grappling with how best to support students with anxiety, depression, trauma, and even suicidal ideation (Jones, 2020). Loretta Whitson, executive director of the California Association of School Counselors, pointed to the important role counselors play in the lives of students: “School counselors do triage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…School counselors, because of the long-term relationships they have with students, are uniquely positioned to support students' social/emotional well-being. A limited number of studies on stress and anxiety have been presented in counseling research on cognitive-behavioral programs (Hains, 1994;Sanders et al, 2019), relaxation techniques (Hiebert & Eby, 1985;Laselle & Russell, 1993), meditation and mindfulness (Laselle & Russell, 1993;Su & Swank, 2019), and yoga (Taylor et al, 2019). Although many of the studies have focused on elementary students, the research with high school students demonstrated that effective stress management programs have positive mental, physical, and academic benefits for students in that age range (Hains, 1994;Taylor et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga has also been integrated into a school counseling program. A qualitative study with the school counselors who ran the program reported that the students became more aware of their thoughts and feelings and, when stressed, they also practiced the yogic breathing outside of class (Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%